GENIUS LEARNING STRATEGY PADA PEMBELAJARAN IPS DI SD SE KECEMATAN BUAY MADANG OKU TIMUR - Hendy Pratama (LP2M STIT Al-Hikmah Way Kanan, 2020)
Abstract This study aims to determine the use of genius learning strategies to improve motivation and social studies learning outcomes of students in class V SDN 1 Buay Madang. This type of research is classroom action research (CAR). The results of this study are in the first cycle of students who succeeded in as many as 10 people (40%) and students who have not completed as many as 15 people (60%) with an average score of 62.8. Students who have received good grades in the aspect of not being easily satisfied with the achievements they have reached 166 students with a percentage of 64% it shows a low level of student motivation. In the second cycle overall students complete 100% with an average value of 75.8. Some of the indicators that have increased motivation from the 14 indicators get a percentage of ≥80% and get a very good predicate. Thus the use of genius learning strategies can increase motivation and social learning outcomes of students in class V SDN 01 Buay Madang Keywords: Genius Learning, IPS